A case study of poly (aryl ether sulfone) hemodialysis membrane interactions with human blood: Molecular dynamics simulation and experimental analyses. (December 2020) - Mollahosseini, Arash; Argumeedi, Srija; Abdelrasoul, Amira; Shoker, Ahmed
Highlights: PAES hemodialysis membrane was selected for blood-membrane interaction study. Blood- membrane interactions were investigated using spectroscopy analyses. PAES morphological variation and blood attachments clots were investigated. Binding energy between human serum proteins and PAES was studied using MDS. Abstract: Patients with end-stage renal diseases (ESRD) require specific health cares as the accumulation of toxins due to the lack of kidney functionality would affect their lives. However, the mortality rate is still high due to cardiovascular diseases, socks, etc. A majority of patients with chronic kidney disease (CKD) require hemodialysis services. Blood purifying membranes, as the main component of hemodialysis setups, however, still suffer from lack of optimum biocompatibility, which results in morbidity and mortality of hemodialysis service receiving patients. The goal of the present case study is to have an in-depth understanding of the current blood-hemodialysis membrane interactions occurring during hemodialysis sessions using poly (aryl ether sulfone)-poly (vinyl pyrrolidone) (PAES-PVP) membrane. Attenuated total reflectance-Fourier transmission infrared (ATR-FTIR) spectroscopy, Raman spectroscopy, and solid-state nuclear magnetic resonance (SSNMR) spectroscopy were used to assess the initial chemical structure of the PAES-PVP membrane along with the variations after with the infections with human blood. Furthermore, scanning electron microscopy (SEM) and Transition electron microscopy (TEM) were used to visualize the structural variation of the membrane, blood aggregations, and blood clots on the membrane surface. Besides, Molecular dynamics (MD) simulation was used to assess the interaction of PAES-PVP with major human blood proteins, in terms of interaction energy, which is a novel contribution to the area. The macromolecules (human serum albumin (HSA), human serum transferrin (TRF), and human fibrinogen (HFG)) were chosen from the plasma protein component. These protein structures were chosen based on their different molecular size. Three advanced spectroscopy techniques and two advanced visualization techniques were used for the assessment of the membranes. Spectroscopy studies revealed amine related peak displacement and intensity shifts as indices for attachment of biological species to the polymeric membrane surfaces. Raman peaks around 370, 798, and 1299 cm −1, which experienced significant shifts that were related to carbon-nitrogen and sulfur-oxygen bonds due to protein adhesion. Visualization techniques illustrated blood protein fouling patterns and extracellular vesicles' presence in the pore structures into membranes. The findings highlight the importance of whole structure biocompatibility improvement, rather than only focusing on surface modifications of hemodialysis membranes. Molecular dynamics simulation assessment showed various interaction behaviors for different proteins suggesting molecular weight and active residues of the protein macromolecules play an important role in interacting with polymeric structure. FB had the highest interaction (4, 274, 749.07 kcal/mol) and binding (10, 370.90 kcal/mol) energy with the PAES-PVP structure. TRF owned the lowest interaction energy with respect to its lower molecular weight and fewer active residue count. Graphical abstract: Image, graphical abstract Computational and experimental assessment of poly aryl ether sulfone structure for hemodialysis application.